2019
DOI: 10.3390/su11092537
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Viewing Photos of Different Types of Rural Landscapes on Stress in Beijing

Abstract: The environment can affect people’s health by relieving stress, and rural landscape as a special environment might influence human’s stress relief. This study takes different types of rural landscapes as the research object to explore their impact on stress levels, which are shown by photos. As an independent variable, the rural landscape is divided into three levels: Type 1 (natural landscape), type 2 (productive landscape), and type 3 (artificial landscape). Seventy-three subjects were randomly assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
3
5
1
Order By: Relevance
“…This variation could have been due to a variety of natural factors in the VR of the two environments. This result is compatible with our physiological results and those of several studies related to the effects of forest environments on, e.g., stress relief, emotional situation adaptation, the positive association between health parameters and natural environments, and the positive impact of the forest on the activity of the nervous system (such as autonomic activity) [33,40,41,43,44]. Generally, walking is connected with therapeutic effects, and most people consider it a beneficial activity [45].…”
Section: The Impact Of Virtual Forest Walk On Psychological Responsessupporting
confidence: 92%
See 2 more Smart Citations
“…This variation could have been due to a variety of natural factors in the VR of the two environments. This result is compatible with our physiological results and those of several studies related to the effects of forest environments on, e.g., stress relief, emotional situation adaptation, the positive association between health parameters and natural environments, and the positive impact of the forest on the activity of the nervous system (such as autonomic activity) [33,40,41,43,44]. Generally, walking is connected with therapeutic effects, and most people consider it a beneficial activity [45].…”
Section: The Impact Of Virtual Forest Walk On Psychological Responsessupporting
confidence: 92%
“…The results showed that a realistic environment could substantially positively impact sympathetic activity, resulting in a quicker recovery from stressful situations. These findings were generally consistent with past research that discussed physiological response when exposed to forest environments [24] and the positive effect of rural landscapes on stress [40]. However, the reported high significance in the realistic environment might have been more related to the greenery of scenes compared to the dreamlike environment, which was consistent with previous research findings on the use of green environments to mitigate stress [40,41].…”
Section: The Impact Of Virtual Forest Walk On Physiological Responsessupporting
confidence: 92%
See 1 more Smart Citation
“…First of all, considering the integration of psychological and VR technology, the attention, focus, and cognitive preference in the psychosocial response due to specific anxiety and depression moods have not yet been fully grasped. We failed to discuss the possible effects of attention [130], environmental preference [131], familiarity with the environment, and different types of recreation environments [132] on recovery outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Six different environments (using virtual reality) were assigned to 120 participants randomly, and it was found that natural sceneries had restorative effects on fatigue and negative mood. A study done by Wang et al [25] discovered that water landscapes had a higher positive impact on the stress levels of subjects, compared to other natural environments. In contrast, Tsutsumi et al [26] found that participants were more relaxed after watching forest videos compared to sea videos.…”
Section: Indoor Nature Therapymentioning
confidence: 99%